Analisis Sekolah Ramah Anak dalam Standar Sarana dan Prasarana di SD Muhammadiyah Taman Sidoarjo - Amrullah, Muhlasin; Angela, Mayanksari Nur; Kusumawardhana, Mahardhika Dharmawan; Hikmah, Khizanatul (CV. Creative Tugu Pena, 2022)
The article aims to analyze child-friendly schools in terms of facilities and infrastructure standards at elementary school Muhammadiyah Taman 2 Sidoarjo. This type of research is a qualitative research with a case study research design. The subject of this research is the existing facilities and infrastructure at elementary school Muhammadiyah 2 Taman which was taken using the triangulation technique. Collecting data was taken through interviews, observation, and documentation. The data analysis technique uses a data reduction model, data presentation and drawing conclusions or verification that developed by Miles and Huberman (2016). The results showed that the standard of facilities and infrastructure at elementary school Muhammadiyah 2 Taman had met the standards of child-friendly schools. Among the existing facilities the school meets the standard of facilities and infrastructure by having a land area of ??1562 m² and has a 3-story building that is protected from danger and access to evacuation, the building has met the standard of facilities and infrastructure set by the Education office, and there is a permit builder. Complete facilities and infrastructure such as having a classroom, library, laboratorium of. Science, room leadership, teacher's room, place of worship, latrine circulation room, playground, healthy canteen, symbol of a child-friendly school, communication media and counseling room that are in accordance with the standards that have been set. Keywords: Child Friendly School, Facilities Standard School, Infrastructure School